2019
DOI: 10.3390/rs11232867
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Ionospheric Scintillation Effects on GNSS Signals with VMD-MFDFA

Abstract: Severe scintillations degrade the satellite signal intensity below the fade margin of satellite receivers thereby resulting in failure of communication, positioning, and navigational services. The performance of satellite receivers is obviously restricted by ionospheric scintillation effects, which may lead to signal degradation primarily due to the refraction, reflection, and scattering of radio signals. Thus, there is a need to develop an ionospheric scintillation detection and mitigation technique for robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For a while now, the geophysical and medical industries have used Multifractal Detrended Fluctuation Analysis (MFDFA) to identify self-similarities and long-range correlations in the signals. Research found that using VMD and MFDFA together allowed for the estimation, mitigation, and re-acquisition of GNSS signals even when ionospheric scintillation effects were intense [9].…”
Section: Variational Mode Decomposition (Vmd) and Multifractal Detren...mentioning
confidence: 99%
See 2 more Smart Citations
“…For a while now, the geophysical and medical industries have used Multifractal Detrended Fluctuation Analysis (MFDFA) to identify self-similarities and long-range correlations in the signals. Research found that using VMD and MFDFA together allowed for the estimation, mitigation, and re-acquisition of GNSS signals even when ionospheric scintillation effects were intense [9].…”
Section: Variational Mode Decomposition (Vmd) and Multifractal Detren...mentioning
confidence: 99%
“…The purpose of VMD is to deal with the variational problem of signals in all its forms, build noise-free IMFs, and eliminate them. In order to address the fluctuation (variational) problem of signals caused by obstructions and atmospheric disturbances, the VMD decomposition procedure was developed [9]. A time-frequency approach known as VMD in conjunction with MFDFA was used to examine how well GNSS receivers performed when subjected to ionospheric scintillation effects.…”
Section: Variational Mode Decomposition (Vmd) and Multifractal Detren...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has significant advantages in processing nonrecursive signals and not only can overcome the mode aliasing problem in EMD but also can use its own Wiener filtering characteristics to obtain a better filtering effect. VMD has received a lot of attention from researchers and has been successfully applied to many fields such as mechanical diagnosis, biomedical science, and other signal processing [18][19][20]. Although VMD obtains excellent results in signal denoising, these effects are determined by two critical parameters, namely, the number of modes K and the value of the penalty factor α, which are usually selected within a certain range.…”
Section: Introductionmentioning
confidence: 99%
“…8 Ionospheric scintillation is a phenomenon, which occurs in the ionosphere due to rapid fluctuation in the amplitude level, phase, and arrival angle (refractive index of the propagating medium) of the received radio waves. 9 The combined effects of ionospheric scintillation and multipath fading are of great concern as it leads to cycle slip, loss of radio communication, and increased communication errors. Ionospheric scintillation is modelled as Rician fading while multipath by Rayleigh fading.…”
mentioning
confidence: 99%